Mouse transgenesis in a single locus with independent regulation for multiple fluorophores. - Joseph D Dougherty (PLoS ONE, 2012)
A major barrier to complex experimental design in mouse genetics is the allele problem: combining three or more alleles is time-consuming and inefficient. Here, we solve this problem for transgenic animals with a simple modification of existing BAC transgenesis protocols, and generate triple-colored 'prism' mice in which the major cell types of the brain: neurons, astrocytes, and oligodendrocytes, are each labeled with a distinct fluorophore. All three fluorophores are expressed from the same locus, yet each fluorophore is expressed in an independent temporal and spatial pattern. All three transgenes are generally co-inherited across multiple generations with stable genomic copy number and expression patterns. This generic solution should permit more sophisticated experimental manipulations to assess functional interactions amongst populations of cell types in vivo in a more rapid and efficient manner.